2001
DOI: 10.1523/jneurosci.21-21-08339.2001
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 and a Cytosolic Tyrosine Kinase Activate Chloride Outward Transport during Maturation of Hippocampal Neurons

Abstract: The development of hyperpolarizing inhibition is an important step in the maturation of neuronal networks. Hyperpolarizing inhibition requires Cl(-) outward transport that is accomplished by KCC2, a K(+)/Cl(-) cotransporter. We show that cultured hippocampal neurons initially contain an inactive form of the KCC2 protein, which becomes activated during subsequent maturation of the neurons. We also show that this process is accelerated by transient stimulation of IGF-1 receptors. Because the transporter can be r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
127
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 133 publications
(131 citation statements)
references
References 45 publications
3
127
1
Order By: Relevance
“…Elsewhere in the adult CNS, GABA A and GABA C receptor activation can evoke both depolarizing and hyperpolarizing postsynaptic potentials from the same neuron (31). Moreover, different compartments of a single neuron have been reported to contain different intracellular chloride concentrations (32,33) in a manner that is consistent with the differential distribution of the Na-K-Cl and K-Cl cotransporters in the membranes of the proximal and distal portions of the dendrites, respectively. In addition, SAC dendrites exhibit a differential distribution of synaptic proteins because synaptic specializations are present on the distal, and not proximal, portions of their dendrites (20,27,28).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Elsewhere in the adult CNS, GABA A and GABA C receptor activation can evoke both depolarizing and hyperpolarizing postsynaptic potentials from the same neuron (31). Moreover, different compartments of a single neuron have been reported to contain different intracellular chloride concentrations (32,33) in a manner that is consistent with the differential distribution of the Na-K-Cl and K-Cl cotransporters in the membranes of the proximal and distal portions of the dendrites, respectively. In addition, SAC dendrites exhibit a differential distribution of synaptic proteins because synaptic specializations are present on the distal, and not proximal, portions of their dendrites (20,27,28).…”
Section: Discussionmentioning
confidence: 79%
“…Finally, the results suggest that subcellular specializations, such as the differential distribution of the Na-K-Cl and K-Cl cotransporters, can mediate the neural computation of complex information. As occurs in the retina, it is likely that the differential distribution of the Na-K-Cl and K-Cl cotransporters may also mediate neural computations elsewhere in the brain, such as in the midbrain and hippocampus, where the processes of individual neurons exhibit a chloride gradient (32,33). Indeed, the asymmetric release of GABA from interneurons in the brain at dendrodendritic synapses may be an important means by which the brain processes information.…”
Section: Discussionmentioning
confidence: 99%
“…In RVD, Src family kinases were reported to regulate large conductance channels [activation of BK Ca ; (25) ], voltage-dependent potassium channels [both activation and inhibition were described; (26,27) ], and swelling-activated anion channels [ (20) , reviewed in (4) ]. In addition, the Src family kinase-dependent activation of the electroneutral K + -Cl -symport in hippocampal neurons (28) and the rapid efflux of organic solutes, such as amino acids, sugars, methylamines, and polyols, via the volume-sensitive organic osmolyte-anion channel (29) were discussed to contribute to RVD. In the perfused rat, liver swellinginduced activation of p38 MAPK is involved in RVD, whereas p38 MAPK is apparently not involved in the net K + release induced by oxidative stress (30) .…”
Section: Src Family Kinases and Cell Volume Regulationmentioning
confidence: 99%
“…Furthermore, this study suggests that KCC2 influences synchronization in the functional development of glutamatergic and GABAergic synapses in neurons. Moreover, KCC2 expression was shown to be correlated with synaptogenesis (Gulyás et al, 2001;Zhang et al, 2006), and fast kinetics of KCC2 activity regulation was shown (Kelsch et al, 2001;Rivera et al, 2004). Based on this, alterations in KCC2 may influence hippocampal and cortical plasticity and network activity, thereby affecting the trophic role of GABA in development (Ben-Ari, 2002;Owens and Kriegstein, 2002;Represa and Ben-Ari, 2005).…”
Section: Figurementioning
confidence: 94%
“…Thus, the ability of Cl À co-transporters to influence the inhibitory function of GABA A potentials is determined by additional regulatory mechanisms of KCC2, which should be taken into consideration when determining the GABAergic molecular phenotype. Such post-translational modifications include oligomerization, membrane integration, and phosphorylation (Balakrishnan et al, 2003;Blaesse et al, 2006;Kelsch et al, 2001;Lee et al, 2007;Zhang et al, 2006). Because Cl À homeostasis is determined by both NKCC1 and KCC2, we examined the interaction between these transporters as expressed by the ratio of KCC2/NKCC1 in crude cytoplasmic fraction (S2) and in the plasmamembrane-enriched fraction (LP1).…”
Section: Figurementioning
confidence: 99%